Proposal and Performance Evaluation of a Magneto-Striction Type Torque Sensor Consisting of Small-Sized Coils Connected in Series. (5th September 2012) - Tsujisawa, Takahiko; Yamakawa, Kazuhiro
Abstract : We propose a sensor consisting of small-sized coils connected in series and a detection method for the sensor based on the iteration of the periodic time difference. The evaluation results are also presented and show the effectiveness of the proposed system. The target performance of the sensor is as follows: (i) a detection range from 0 to ±100 Nm, (ii) a hysteresis error of less than 1%, (iii) an angular-dependent noise of less than 2%, and (iv) a sensor drift of less than 2%. From the evaluation results, it is clear that these performance targets, as well as a sufficient response time, are realized.